Penggunaan Bahasa Penyiar Radio di Daerah Istimewa Yogyakarta - nfn Riani (Balai Bahasa Provinsi Riau, 2018)
The linguistic situation in the Daerah Istimewa Yogyakarta is influenced by language contact, diglosia, and bilingualism because there are three languages in the community, namely Indonesian, regional, and foreign language. In this situation, there are linguistic symptoms such as code mixing and code switching, there is no exception to radio broadcaster’s language use. In fact, broadcaster is an agent who has an important role and influence in spreading of Indonesian in DIY. Therefore, this study discusses and describes how radio broadcaster’s language use in Daerah Khusus Yogyakarta and what factors influence it. This study is descriptive. The data in this study is radio broadcaster’s language use in several programs recorded in February—April 2017. The result of the analysis shows that broadcaster’s language use is influenced by nonlinguistic factors which include topic, participant, community participant, situation, goal, action, tone of voice, speech tool, and the norm of speaking. Topic plays a more dominant role than other nonlinguistic factors. The broadcaster uses formal Indonesian spoken speech and a little of code switching to Arabic when delivering serious topics, such as news topics. Meanwhile, the broadcaster use non-formal spoken Indonesian and more code switching, such as into English or Javanese when bringing relaxing events, such as entertainment topics.